The impact of obesity on dementia - Wojciechowska, Adriana; Mądry, Wojciech; Mazurkiewicz, Aleksandra; Marcicka, Justyna; Kołodziej, Magdalena; Męczyńska, Joanna; Saiuk, Nazarii; Kozicz, Michał Andrzej; Seredyński, Tomasz; Salasa, Weronika (Journal of Education, Health and Sport, 2024)
Introduction Dementia is a syndrome characterized by a gradual deterioration of cognitive functions, including memory, thinking, orientation, attention span, perception, judgment, and language abilities. Obesity influences its development. Materials and methods The following review of studies is based on recent scientific articles available in PubMed and Google Scholar databases.The most searched phrases included: "dementia", "obesity", "midlife",and "the relationship between obesity and the risk of dementia". Results Literature review indicates the existence of a relationship between midlife obesity and later dementia. It has also been pointed out that the forecasts for the onset of obesity and dementia are alarmingly rising world wide.It is estimated that by the year 2050, we can expect a threefold increase in dementia cases. Conclusion The results of the cited studies indicate that further research into the occurrence of obesity and its later association with dementia is necessary. Midlife obesity likely plays a significant role in the etiopathogenesis of dementia.